Immediate effects of the activation of the affected lower limb on the balance and trunk mobility of hemiplegic stroke patients - Kim, Young-dong (J Phys Ther Sci, 2015)
[Purpose] The purpose of this study was to determine the effects of the activation of the affected lower limb on balance and the trunk hemiplegic mobility of stroke patients. [Subjects] The gait group (GG) consisted of 6 subjects with hemiplegia and the non-gait group (NGG) consisted of 6 hemiplegic subjects. [Methods] The subjects in both groups were given foot facilitation training once for 30 min. The Spinal Mouse was used to measure the spinal alignment and the Berg balance scale (BBS) and sensory tests were also performed. [Results] In the GG, the sacral hip in upright to flexion, the lumbar spine in upright to extension, and the sacral hip and lumbar spine in flexion to extension showed significant increases in their angles after the intervention. In addition, there was a significant increase in the angle of the lumbar spine during extension from an upright position in the NGG. The BBS scores of both groups also increased significantly. [Conclusion] The intervention resulted in improvements in the angle of anterior pelvic tilt in the GG, and subjects in the NGG showed more extension of the thorax, which was regarded as compensation to avoid falling forward when flexing from an upright position. However, when extending backward from an upright position, both groups tended to control balance by using more lumbar flexion to keep the center of mass (COM) within the base of support (BOS). Both groups had better BBS scores.